CARDIAC PARAGANGLIOMAS: TWO PATIENTS WITH DIFFERENT GERMLINE MUTATIONS - Tai, YT; Lau, Eunice YC; Lim, SW; Hussein, Z (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Cardiac paragangliomas (CPGLs) are rare, accounting for 2% of all PGLs and 1–3% of all primary cardiac tumours. Following biochemical evaluation, anatomical and functional imaging are necessary. Definitive treatment is determined by tumour resectability, presence of multiple PGL with/without metastases. We report two cases, both associated with genetic mutations. RESULTS Patient 1, diagnosed with bilateral CPGLs at age 38 and underwent bilateral neck resection. Tumour histopathology were consistent with PGLs. At age 45, he presented with severe hypertension, elevated urinary noradrenaline >20 times and a mass adjacent to main pulmonary artery (PA) on CT imaging which was deemed inoperable. Coronary angiogram revealed a vascular cardiac mass adjacent to PA and proceeded with tumour embolization with helical coil placement in main feeder artery and alcohol ablation. This resulted in tumour size reduction, resolution of hormonal excess and hypertension. He later developed disease progression with recurrence in right carotid and metastases to aortocaval nodes and spine. Following 4 cycles of PRRT, there was clinical, biochemical and radiological improvement. Genetic testing showed KIF1B mutation. His younger sibling had bilateral carotid and abdominal PGLs. Patient 2 is 23-years-old, presented with hypertensive emergency and had elevated urinary normetanephrines >10 times. CT abdomen showed bilateral adrenal masses and left renal mass. Ga-68-DOTATATE-PETCT revealed disease at left carotid, cardiac and bilateral adrenal glands. She underwent bilateral adrenalectomy with left cortical sparing and left nephrectomy. Histopathology confirmed bilateral pheochromocytomas and left kidney leiomyoma. Postoperatively, hypertension persisted with better control. MRI imaging confirmed PGLs at left carotid, vagal and atrioventricular groove (cardiac). She is currently being monitored with future consideration for tumour resection. Genetic testing showed SDHD mutation with a family history of carotid PGLs in her paternal relatives. CONCLUSION These two cases highlight the importance of multidisciplinary approach in the management of CPGLs, as part of a hereditary paraganglioma–pheochromocytoma syndrome.